Características qualitativas da carne de cordeiros 1/2 Dorper +1/2 Santa Inês abatidos com diferentes espessuras de gordura subcutânea - Santos, Camilo Azevedo (2018)
The study evaluated the allometric growth of commercial cuts, tissue composition, leg muscle index and physical-chemical characteristics of lambs ½ Dorper + ½ Santa Inês slaughtered at 2.0; 3.0 and 4.0 mm subcutaneous fat thickness (SFT). The experiment was carried out in partnership with Fazenda Canafístula, located in the state of Sergipe, county of Nossa Senhora das Dores. Weaned at the same breeding season, 24 male, uncastrated, ½ Dorper + ½ Santa Inês lambs were randomly assigned and confined to three collective bays. In periods of 15 days, the animals were weighed and their SFT measured. The lambs were slaughtered with stipulated SFT. The carcasses, after skinning and evisceration, were stored in a cold room for 24 hours at a temperature of 4 ° C. The carcasses were sectioned longitudinally to the vertebrae. The left half carcass was weighed and separated into five commercial cuts: neck, shoulder, rib, loin and leg. After dissection of the cuts, muscle, subcutaneous fat, intermuscular fat and bone were weighed, in addition to the muscle index of the leg. Allometric growth was determined as a function of the commercial cuts in relation to the halfcarcass, and then according to the tissue components in relation to the respective commercial cut. For the physicochemical characteristics of the meat the parameters of pHinitial and pHfinal were collected, respectively. In addition, the SFT were measured by ultrasound, pachymeter and through photographs of the Longissimus dorsi muscle between the 12th and 13th vertebrae. Meat and subcutaneous fat measurements were also performed for the parameters of brightness, red intensity, yellow intensity (L *, a * and b *), respectively, and then calculated tonality and chroma. Images were analyzed using the ImageJ® software in the Longissimus dorsi muscle between the 12th and 13th ribs, obtaining data such as the loin eye area (AOL), depth, length and marbling degree of this muscle. For the chemical characteristics, moisture, protein, ashes and total lipids were submitted to analysis of variance and submitted to the Student test with significance (P <0.05). For neck cuts, lambs with 2.0 and 4.0 mm SFT showed early growth, different from lambs slaughtered with 3.0 mm SFT. For the shoulder cut, animals with 2.0 and 4.0 mm showed to have an early growth. However, the palette of animals with 3.0 mm SFT had late growth. The rib showed isogonic growth for lambs with 2.0 and 3.0 mm EGS. Differently from the animals that were slaughtered with 4.0 mm of SFT, which had an early growth. In the cut loin, lambs with 2.0 and 3.0 mm had negative heterogenic growth. This did not occur with lambs with 4.0 mm, which showed a growth proportional to half-carcass. The leg was the cut that presented early growth for the animals slaughtered with different SFT and was the cut that best correlated with the half-carcass. However, SFT at slaughter, measured with a caliper, showed differences for 2.0 mm, 3.0 mm and 4.0 mm SFT. Regarding the measurement of SFT by photograph, difference was observed only for the treatment with 2.0 mm of SFT. The other characteristics did not present differences between slaughtered lambs with different SFT. Due to the allometric growth, it is recommended the slaughter of ½ Dorper + ½ Santa Inês lambs, with 4.0 mm of EGS, for presenting better yields of cuts of palette and leg, at the same time that the quality of the meat did not present alterations physico-chemical characteristics.